P17 Anti-neuronal antibodies in patients with systemic lupus erythematosus: prevalence, clinical associations and searching for a specific target. (23rd March 2020) - Chessa, Elisabetta; Angioni, Maria Maddalena; Pinna, Silvia; Congia, Mattia; Floris, Alberto; Manca, Elias; Corda, Giulia; Lorefice, Lorena; Ferri, Gian Luca; Cocco, Cristina; Mathieu, Alessandro; Cauli, Alberto; et al.
Abstract : Background: The aim of this study was to evaluate the prevalence and clinical significance of Anti-neuronal antibodies (AnAb) in a cohort of neuropsychiatric (NP) Systemic Lupus Erythematosus (SLE) patients. Methods: Overall, 28 SLE patients (age 45.6 ± 14.4 years) with inflammatory neuropsychiatric syndromes, classified according to existing criteria (1, 2) were enrolled and serum samples were collected before starting treatment for the specific NP event; 41 consecutive SLE patients (44.2 ± 14.2 years) without NP involvement, 22 Multiple Sclerosis patients (37.9 ± 11.0 years) and 82 healthy subjects (44.8 ± 15.0 years) served as controls. Search for AnAb was performed by tissue-based immunohistochemistry assays (IHC) on male Sprague Dawley rat's brain sections and confirmed by cell-based immunocytochemistry assays on SH-SY5Y (human neuroblastoma) cell cultures. The association between serum positivity for AnAb by IHC and a large panel of data (demographic, serologic, SLEDAI, conventional brain MRI, treatment) was investigated by univariate analysis. Multivariate models were fitted with covariates with p<0.05 to identify factors independently associated with serum positivity for AnAb; p<0.05 were considered statistically significant. Results: AnAb were detected in 23 (82.1%) NPSLE patients and in 16 (39.0%) SLE patients without NP involvement resulting in 82% specificity (95%CI 71%-90%) and 61% sensitivity (95%CI 48%-72%) in differentiating NPSLE from SLE without NP involvement. None of the sera from MS patients (0%) and healthy subjects (0%) showed AnAb. Serum AnAb by IHC were independently associated with NPSLE (p<0.01) and higher SLEDAI (p<0.01). No association with specific NPSLE syndrome and brain conventional MRI abnormalities was identified. Conclusion: AnAb are significantly more frequent in patients with NPSLE than SLE. Further studies are needed to identify the unknown neuronal antigens targeted by AnAb in SLE patients.